تأثير حمض الهيوميك ومستخلص الطحالب البحرية على النمو الخضري وجودة الشعير (Comprehensive Journal of Science, 2025)
The study aimed to explore the role of transparency and accountability in reducing administrative corruption through the following key aspects: identifying the impact of administrative transparency on limiting corruption practices within public institutions; examining the role of accountability mechanisms in enhancing administrative efficiency and combating corruption; understanding the complementary relationship between transparency and accountability in building an ethical administrative environment; and identifying the main challenges hindering the implementation of transparency and accountability in administrative institutions, particularly in Arab contexts. The researcher adopted the descriptive methodology due to its suitability for the study’s objectives. The study reached the following conclusions:• Weak legal and regulatory frameworks limit the implementation of transparency and accountability principles, creating opportunities for the spread of corruption within administrative institutions.• The absence of an institutional culture that supports transparency and accountability contributes to the concealment of errors and corruption, and undermines employees’ ability to report misconduct.• The lack of independence and capacity of oversight and supervisory bodies reduces their effectiveness in detecting violations and holding officials accountable, negatively affecting public trust in the administrative system.•           Weak societal awareness and limited public participation in oversight reduce the societal pressure needed to promote transparency and accountability, leaving institutions vulnerable to mismanagement and corruption
Keywords: Transparency and Accountability – Administrative Corruption